2015
DOI: 10.1002/micr.22386
|View full text |Cite
|
Sign up to set email alerts
|

Thoracodorsal nerve transfer for triceps reinnervation in partial brachial plexus injuries

Abstract: Direct TDN transfer might be a valid surgical procedure for the restoration of elbow extension in patients with partial BPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…4,10,11 The thoracodorsal nerve can restore elbow extension in partial BPI, but it was not available in any of our patients. 4 Flores 10 reported that M3 or more strength was achieved in all of his patients in whom he performed transfer of the medial pectoral nerve to the radial nerve or to the nerve to the upper medial and long heads of the triceps, with or without an interpositional nerve graft. Drawbacks of this technique are weakening of forceful adduction of the limb against the trunk and the need for a nerve graft.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…4,10,11 The thoracodorsal nerve can restore elbow extension in partial BPI, but it was not available in any of our patients. 4 Flores 10 reported that M3 or more strength was achieved in all of his patients in whom he performed transfer of the medial pectoral nerve to the radial nerve or to the nerve to the upper medial and long heads of the triceps, with or without an interpositional nerve graft. Drawbacks of this technique are weakening of forceful adduction of the limb against the trunk and the need for a nerve graft.…”
Section: Discussionmentioning
confidence: 67%
“…1e3 It improves hand function because a functional triceps can modulate forearm and hand positioning by counteracting the elbow flexors' vector movement, resulting in increased accuracy. 4 Several nerve transfers can restore triceps function in patients with partial paralysis of the upper limb, including transfers of the axillary nerve, the thoracodorsal nerve, the nerve to the brachialis, the fascicles of the ulnar nerve, the medial pectoral nerve, and the phrenic nerve. 3e11 In partial but extended lesions that combine root and cord lesions with involvement of the posterior cord, many of these nerve transfers might not be available.…”
mentioning
confidence: 99%
“…Recommended if the Oberlin procedure is not possible [110,111]. Not advised in the case of a weak shoulder adduction or if a muscle transfer is planned.…”
Section: Tdn To Mcn Transfermentioning
confidence: 99%
“…The best results have been obtained by transferring the TMN to the TLH [116,117]. Other possibilities are to re-innervate the TLH with ICNs [24,92,118,119], a UN fascicle [24], the MPN [120], TDN [111], PHN [121], contralateral C 7 nerve root [122] and an RAN fascicle for the hand [123]. The results have been poor, particularly the ICNs [119].…”
Section: Elbow Extension Nerve Transfersmentioning
confidence: 99%
“…This yielded M4 elbow extension recovery in 7 of 8 patients with a high radial nerve injury. 21 Alternatively, the nerve to the brachialis muscle might be used as a donor for transfer. 2 Concerning orthopedic procedures, elbow extension is most commonly reconstructed by means of posterior deltoid or biceps muscle transfer to the triceps.…”
mentioning
confidence: 99%